My garden in the wilderness - Murray, Kathleen L. (Cambridge library collection. Botany and horticulture, 2016)
This story of an Indian garden was published in 1915. Its author, Kathleen L. Murray, was living in the remote north-eastern region of Bihar in the home of her brother, an indigo producer, and some of her musings on life and gardening in India had already been published in the periodical The Statesman. She viewed this work not as a guide, but 'merely a rambling record of some years in a garden' which combined European plants such as roses and sweet peas with natives such as cannas and beaumontias. Along with her gardening successes and failures over three years, the book provides insights into the life of the European woman in India - with no employment, and required to be both idle and aloof from the lives of the wider population. Murray's descriptive powers and enthusiasm for her garden make this book both enjoyable and evocative of imperial India